(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Load shedding refers to a system for which electric energy demand is distributed among several power sources. Load shedding is used to reduce the strain on the energy source to the greatest extent possible when the energy demand exceeds what the power source can supply. A service provider sells power to a client. Traditional load shedding methods, and even under voltage regulation, have a longer reaction time and are inconsistent in properly distributing load in the case of any interruptions or failures. This causes an increase or reduction in load, resulting in an inability to meet the energy demand. The study, titled Intelligent Load Shedding, focused on a more contemporary approach to load shedding. A thorough comparison of conventional versus intelligent load shedding methods was conducted from the perspectives of operation design, engineering and implementation. It consumes remained revealed that the intelligent technique of load shedding overcomes all of the disadvantages of traditional techniques, is extremely efficient, and requires very little maintenance.